Move the forces uprooting us - Khanna, Parag (Scribner, 2021)
Prologue : Where will you live in 2050? -- Mobility is destiny -- The war for young talent -- Generation move -- The next American dream -- The European Commonwealth -- Bridging regions -- Northism -- Will "the south" survive? -- The Asians are coming -- Retreat and renewal in Pacific Asia -- Quantum people -- 'Pax urbanica' -- Civilization 3.0